2008
DOI: 10.1038/npp.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Circadian Output Molecule Prokineticin 2 Results in Anxiolytic and Antidepressant-like Effects in Mice

Abstract: Disrupted circadian rhythms are strictly associated with mood disorders. The suprachiasmatic nucleus (SCN) is the master pacemaker that drives circadian rhythms in mammals. However, the underlying molecular connections of circadian rhythm and mood disorders are still poorly understood. Prokineticin 2 (PK2) is a signaling molecule that is critical for transmitting the circadian rhythms from the SCN. Previously, it is has been shown that the receptor for PK2 is expressed in virtually all of the primary SCN targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…A recent animal study reported that PK2 gene deficit mice showed disruptions in the homeostatic regulation of sleep, such as reduced non-rapid eye movement sleep time and increased rapid eye movement (REM) sleep time in both light and dark periods (Hu et al 2007). Mice lacking the PK2 gene also showed significantly reduced anxiety and depressionlike behaviors in the forced swimming test (Li et al 2009). In addition, PK2 gene deficit mice showed deceased responses to new environments in terms of locomotor activity, arousal, body temperature, and food intake (Li et al 2009).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent animal study reported that PK2 gene deficit mice showed disruptions in the homeostatic regulation of sleep, such as reduced non-rapid eye movement sleep time and increased rapid eye movement (REM) sleep time in both light and dark periods (Hu et al 2007). Mice lacking the PK2 gene also showed significantly reduced anxiety and depressionlike behaviors in the forced swimming test (Li et al 2009). In addition, PK2 gene deficit mice showed deceased responses to new environments in terms of locomotor activity, arousal, body temperature, and food intake (Li et al 2009).…”
Section: Introductionmentioning
confidence: 96%
“…Mice lacking the PK2 gene also showed significantly reduced anxiety and depressionlike behaviors in the forced swimming test (Li et al 2009). In addition, PK2 gene deficit mice showed deceased responses to new environments in terms of locomotor activity, arousal, body temperature, and food intake (Li et al 2009). On the other hand, PK2 receptor, a G-coupled receptor for PK2 expressed in SCN and its targets (Cheng et al 2002), has also been shown to be essential for circadian behavior control; PK2 receptor gene mutant mice showed disrupted circadian coordination of the activity cycle and lost precision in the timing of the onset of nocturnal locomotor activity (Prosser et al 2007).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…They also induce cell motility such as angiogenesis (LeCouter and Ferrara, 2002), neurogenesis (Ng, et al, 2005), hemotopoiesis (LeCouter, et al, 2004), neovasculogenesis (Urayama, et al, 2008). Prokineticins regulate complex behaviors such as feeding (Negri, et al, 2004), drinking (Negri, et al, 2004), anxiolity (Li, et al, 2009). Moreover, prokineticins are potent survival/mitogenic factors for various cells including endothelial cells , neuronal cells (Kisliouk, et al, 2005;Ngan, et al, 2007a), lymphocytes, hematopoietic stem cells (LeCouter, et al, 2004), and cardiomyocytes (Nebigil, 2009).…”
Section: Prokineticins and Cognate Receptorsmentioning
confidence: 99%
“…Prokineticins are a pair of signal factors involved in a variety of physiological processes, including gastrointestinal mobility, circadian rhythms, emotion, nociception, angiogenesis, and neurogenesis (2)(3)(4)(5). Prokinticins execute their functions by binding to two closely related GPCRs, PKR1 and PKR2 (6,7).…”
mentioning
confidence: 99%